Threshold effects and unit roots of real commodity prices since the mid-nineteenth century - Clavijo, Pedro; Campo, Jacobo; Mendoza, Henry (Economics and Business Letters, 2020)
This paper investigates whether a unit root process and nonlinearities can characterize real commodity prices for six major primary goods. An unconstrained two-regime threshold autoregressive model is used with an autoregressive unit root. Among the main results, it is found that terms of trade for agricultural, mineral, non-tropical, and non-oil goods are nonlinear processes that are characterized by a unit root process. The finding of nonlinearities explains why the deterioration of the terms of trade has been episodic. Additionally, we found there is no statistical evidence supporting the Prebisch-Singer hypothesis for agricultural, mineral, non-tropical, and non-oil goods.